Enhancing the Oncolytic Activity of CD133-Targeted Measles Virus: Receptor Extension or Chimerism with Vesicular Stomatitis Virus Are Most Effective - Kleinlützum, Dina; Hanauer, Julia D. S.; Muik, Alexander; Hanschmann, Kay-Martin; Kays, Sarah-Katharina; Ayala-Breton, Camilo; Peng, Kah-Whye; Mühlebach, Michael D.; Abel, Tobias; Buchholz, Christian J. (Frontiers in Oncology, 2017)
Therapy resistance and tumor recurrence are often linked to a small refractory and highly tumorigenic subpopulation of neoplastic cells, known as cancer stem cells (CSCs). A putative marker of CSCs is CD133 (prominin-1). We have previously described a CD133-targeted oncolytic measles virus (MV-CD133) as a promising approach to specifically eliminate CD133-positive tumor cells. Selectivity was introduced at the level of cell entry by an engineered MV hemagglutinin (H). The H protein was blinded for its native receptors and displayed a CD133-specific single-chain antibody fragment (scFv) as targeting domain. Interestingly, MV-CD133 was more active in killing CD133-positive tumors than the unmodified MV-NSe despite being highly selective for its target cells. To further enhance the antitumoral activity of MV-CD133, we here pursued arming technologies, receptor extension, and chimeras between MV-CD133 and vesicular stomatitis virus (VSV). All newly generated viruses including VSV-CD133 were highly selective in eliminating CD133-positive cells. MV-CD46/CD133 killed in addition CD133-negative cells being positive for the MV receptors. In an orthotopic glioma model, MV-CD46/CD133 and MVSCD-CD133, which encodes the super cytosine deaminase, were most effective. Notably, VSV-CD133 caused fatal neurotoxicity in this tumor model. Use of CD133 as receptor could be excluded as being causative. In a subcutaneous tumor model of hepatocellular cancer, VSV-CD133 revealed the most potent oncolytic activity and also significantly prolonged survival of the mice when injected intravenously. Compared to MV-CD133, VSV-CD133 infected a more than 104-fold larger area of the tumor within the same time period. Our data not only suggest new concepts and approaches toward enhancing the oncolytic activity of CD133-targeted oncolytic viruses but also raise awareness about careful toxicity testing of novel virus types.